A technical review of the challenges of powder recycling in the laser powder bed fusion additive manufacturing process. Issue 2 (21st January 2021) - Soundarapandiyan, Gowtham; Johnston, Carol; Khan, Raja H.U.; Chen, Bo; Fitzpatrick, Michael E.
Abstract: Laser powder bed fusion (L‐PBF) is one of the most widely used additive manufacturing techniques for fabrication of components with complex geometries for various industrial applications including aerospace, medical and automotive. The unconsumed powder after part manufacturing is often recovered and recycled to improve process efficiency. However, some of the particles in the recycled powder can have different physical and chemical properties from those in the virgin powder owing to their exposure to the complex environment during the manufacturing process. In addition, some contaminants can be introduced in the recycled powder due to poor process control. A number of studies have been published in the past few years revealing the effects of powder recycling on the build properties. The present work aims to highlight the key phenomena during the manufacturing process that caused degradation to the recycled powder. Further to this, some comments, gaps and areas that deserve further detailed studies are also highlighted.